Integration of Antiretroviral Therapy with Tuberculosis Treatment - Abdool Karim, Quarraisha; Abdool Karim, Salim S; Naidoo, Kogieleum; Naidoo, Anushka; Grobler, Anneke; Padayatchi, Nesri; Baxter, Cheryl; Gray, Andrew L; Gengiah, Tanuja; Gengiah, Santhanalakshmi; Jithoo, Niraksha; Nair, Gonasagrie; et al. (The New England journal of medicine, 2011)
In this study from South Africa, earlier initiation of antiretroviral therapy in patients with newly diagnosed HIV infection and TB was associated with higher rates of the immune reconstitution inflammatory syndrome and adverse events but increased AIDS-free survival. In patients who have infection with the human immunodeficiency virus (HIV) and tuberculosis, antiretroviral therapy (ART) may be initiated at the same time as or soon after the initiation of tuberculosis treatment. However, antiretroviral agents are often deferred until after the intensive phase of tuberculosis treatment because of concern about the immune reconstitution inflammatory syndrome (IRIS), 1 , 2 a high pill burden, and overlapping side effects 3 when three antiretroviral agents are added to the standard four antituberculosis drugs. These challenges may result in interruption or discontinuation of treatment for the acquired immunodeficiency syndrome (AIDS) or tuberculosis, which can lead to drug . . .